2016
DOI: 10.1021/acs.inorgchem.5b02860
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization-Dependent Luminescence Properties of Ce:LuPO4

Abstract: The luminescence properties of Ce:LuPO4 depend on both the Ce(3+) center and the host lattice. In this article, we studied the dependence of the luminescence properties of Ce:LuPO4 on both the doping concentration of Ce(3+) and the size and morphology of the LuPO4 matrix at micro- and nanosize regimes. The crystalline behavior of Ce:LuPO4, including its size and shape, was investigated via precursor transformation crystallization. On the basis of this crystallization approach, Ce:LuPO4 hollow nanospheres, nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…The stokes shifts of the 2 F 5/2 to t 2g (1) transition of Ce 3+ ions in CKLC and CKCC crystals were calculated to be 1063 and 1527 cm −1 , respectively. Note that both materials show some overlap of emission and excitation bands, so that Ce 3+ emission may be reabsorbed by another Ce 3+ center, which is similar to previous reports [19].…”
Section: Photoluminescence Spectra and Decay Time Curvesupporting
confidence: 88%
See 1 more Smart Citation
“…The stokes shifts of the 2 F 5/2 to t 2g (1) transition of Ce 3+ ions in CKLC and CKCC crystals were calculated to be 1063 and 1527 cm −1 , respectively. Note that both materials show some overlap of emission and excitation bands, so that Ce 3+ emission may be reabsorbed by another Ce 3+ center, which is similar to previous reports [19].…”
Section: Photoluminescence Spectra and Decay Time Curvesupporting
confidence: 88%
“…5 of 8 bands, so that Ce 3+ emission may be reabsorbed by another Ce 3+ center, which is similar to previous reports [19]. The photoluminescence decay curve of CKLC crystal using an excitation wavelength of 342 nm and a monitoring wavelength of 369 nm is displayed in Figure 5a.…”
Section: R Peer Reviewsupporting
confidence: 87%
“…Rare earth phosphate nanomaterials have been extensively reported due to their high-performance photoluminescence [1,2]. Especially, pure and rare-earth ion doped CePO 4 nanomaterials have received a lot of research interest [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researches have reported on the synthesis of YPO 4 [27], LaPO 4 [28], CePO 4 [29] and GdPO 4 [14] micro/nanomaterials. Compared with a great deal of work on other orthophosphate materials, the study on the synthesis of LuPO 4 material has rarely been reported [3034]. LuPO 4 is an excellent candidate for lanthanide ion substitution because of its favourable physical properties, such as high chemical stability, high melting point, high quantum yield and low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…LuPO 4 is an excellent candidate for lanthanide ion substitution because of its favourable physical properties, such as high chemical stability, high melting point, high quantum yield and low toxicity. Up to now, some typical morphologies of LuPO 4 , such as zero-dimensional nanoparticles [31], microspheres [32], one-dimensional nanorods [30] and three-dimensional microtetrahedron [30], have been successfully synthesized.…”
Section: Introductionmentioning
confidence: 99%